Evaluation of the Zinc Sulfate Catalytic Effect in Empty Fruit Bunches Pyrolysis (2022)
The effect of zinc sulfate as a catalyst on the pyrolysis of empty fruit bunches (EFB) from oil palm was assessed. Thus, a thermo-gravimetric analyzer coupled with a Fourier transform infrared spectroscopy (TG-FTIR) was used, while the percentage of catalyst varied between 0 wt% and 3 wt% at different heating rates (10, 30, and 50 K/min). The kinetic parameters (activation energy, pre-exponential factor, and reaction order) and activation energy distribution were calculated using three kinetic models. The thermogravimetric curves for the EFB pyrolysis showed three prominent peaks in which the maximum mass loss rate was mainly due to cellulose and lignin pyrolysis. On the other hand, FTIR analysis indicated that the main gaseous products were CO2, CO, H2O, CH4, NH3, acids, and aldehydes (CH3COOH). The samples with 2 wt% of catalyst presented higher activation energies in pseudo reactions 1 and 2, ranging between 181,500 kJ/mol–184,000 kJ/mol and 165,200 kJ/mol–165,600 kJ/mol, respectively. It was highlighted that the first pseudo reaction with an activation energy range between 179,500 kJ/mol and 184,000 kJ/mol mainly contributes to the cellulose pyrolysis, and the second pseudo reaction (165,200 kJ/mol–165,600 kJ/mol) could be ascribed to the hemicellulose pyrolysis.